Plasma concentrations of buprenorphine after epidural administration in conscious cats - Duke-Novakovski, Tanya; Clark, Christopher R.; Ambros, Barbara; Gilbert, Peter; Steagall, Paulo V. M. [UNESP] (Elsevier B.V., 2011)
Buprenorphine plasma concentrations were measured after administering buprenorphine (20 mu g/kg) into the lumbosacral epidural space of conscious cats chronically instrumented with an epidural catheter. Blood was collected from a jugular vein before injection and 15, 30, 45 and 60 min and 2, 3, 4, 5, 6, 8, 12 and 24 h after administration. Plasma buprenorphine concentrations were measured using ELISA. Background concentration (before injection) was 1.27 +/- 0.27 ng/mL (mean +/- SD). Including background concentration, the mean peak plasma concentration was obtained 15 min after injection (5.82 +/- 3.75 ng/mL), and ranged from 3.79 to 2.20 ng/mL (30 min-3 h), remaining between 1.93 and 1.77 ng/mL (412 h), and declined to 1.40 +/- 0.62 ng/mL at 24 h. Elimination half-life was 58.8 +/- 40.2 min and clearance 56.7 +/- 21.5 mL/min. Results indicate early rapid systemic uptake of buprenorphine from epidural administration with plasma concentrations similar to using buccal or IM routes by 15 min postinjection. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Buprenorphine; Cat; Epidural; Plasma concentration